Strategi Marketing Communication Brand Startup â€œJujungâ€ dalam Meningkatkan Awareness - Fatmawati, Yeni; Ariyani, Nafiah (International Journal of Demos (IJD), 2023)
AbstractJujung is a new brand in the Triple Play telecommunications industry (Internet, IPTV, Telephony) that focuses on customers in the residential segment. Jujung has an unfamiliar name in the internet industry and has limited marketing area coverage, but Jujung's service sales figures are quite good, Jujung's subscribers currently have nearly 40,000 subscribers. Jujung competes with other big brands such as Indihome, Biznet, First Media, Oxygen, Xl Home, etc. This study aims to find out how Jujung's marketing communication strategy increases brand awareness in the midst of competitive competition. This research is interpretive qualitative (interpretive) with the case study method. The results of this study are that Jujung has carried out a marketing communication strategy starting from re-branding from Jujungnet to Jujung, changing the logo, brand identity to make it look more attractive, creating unique selling points, positioning and communication for marketing communication plans. Jujung made improvements to the Website and Social Media before carrying out the campaign. Digital media (Google Ads) and social media (Instagram & Facebook Ads) are the main media for campaign activities with a segmentation approach according to Jujung's service area coverage. Jujung also carries out outdoor branding activities by placing billboards, billboards, banners, and exhibition activities (Open Booth) which are also segmented and collaborating with the mass media and related communities in the form of sponsorships and special events.Keywords: Jujung, Triple Play, Brand Awareness, Marketing Communication, Digital Marketing.Â AbstrakJujung adalah brand baru di industri telekomunikasi Triple Play (Internet, IPTV, Telephony) yang berfokus pada pelanggan di segmen perumahan. Jujung memiliki nama yang tidak familiar di industri per-internetan dan memiliki keterbatasan cakupan area pemasaran, namun angka penjualan layanan Jujung sangat baik, pelanggan Jujung saat ini telah hampir 40.000. Jujung berkompetisi dengan brand besar lainnya seperti Indihome, Biznet, First Media, Oxygen, Xl Home, dsb. Penelitian ini bertujuan untuk mengetahui bagaimana strategi marketing communication Jujung dalam meningkatkan brand awareness di tengah persaingan yang kompetitif. Penelitian ini bersifat interpretif kualitatif (pemaknaan) dengan metode studi kasus. Hasil dari penelitian ini adalah Jujung melakukan strategi komunikasi pemasaran mulai dari melakukan re-branding dari Jujungnet ke Jujung, mengubah logo, brand identity agar terlihat lebih menarik, membuat unique selling point, positioning dan communication untuk rencana komunikasi pemasaran. Jujung melakukan improvement pada Website dan Social Media sebelum melakukan campaign. Media digital (Google Ads) dan media sosial (Instagram & Facebook Ads) menjadi media utama kegiatan campaign dengan pendekatan segmentasi sesuai cakupan area layanan Jujung. Â Jujung juga melakukan kegiatan outdoor branding dengan penempatan Billboard, Baliho, Spanduk, dan aktivitias exhibition (Open Booth) yang juga bersifat segmented dan menjalin kerjasama dengan media massa dan komunitas terkait dalam bentuk sponsorship dan special event.Keywords: Jujung, Triple Play, Brand Awareness, Komunikasi Pemasaran, Digital Marketing